2020
DOI: 10.21203/rs.2.23095/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of a three-long noncoding RNA prognostic model involved competitive endogenous RNA in kidney renal clear cell carcinoma

Abstract: Background: Lone noncoding RNA (lncRNA) is generally identified as competing endogenous RNA (ceRNA) that plays a vital role in the pathogenesis of kidney renal clear cell carcinoma (KIRC), the most common subtype of renal cell carcinoma with poor prognosis and unclear pathogenesis. This study established a novel ceRNA network and thus identified a three-lncRNA prognostic model in KIRC patients.Methods: Differentially expressed genes (DEGs) were screened out from The Cancer Genome Atlas (TCGA) database. The lnc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…After a careful literature search, we found that the biological process of LINC00460 and LINC01234 in the GILncSig has not been reported to date. We found that the lncRNA LINC00460 was located on chromosome 13q33.2 and is a prognostic biomarker for esophageal squamous cell carcinoma [38] and renal carcinoma [22].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…After a careful literature search, we found that the biological process of LINC00460 and LINC01234 in the GILncSig has not been reported to date. We found that the lncRNA LINC00460 was located on chromosome 13q33.2 and is a prognostic biomarker for esophageal squamous cell carcinoma [38] and renal carcinoma [22].…”
Section: Discussionmentioning
confidence: 87%
“…To determine the accuracy of clinical predictive models related to genome stability, we performed diagnostic test comparisons. Three recently published lncRNA signatures were involved in comparisons: the three-lncRNA signature derived from Zhang et al (Zhang Dan) [22], the four-lncRNA signature derived from Liu et al LiulncSig) [23] and an immune signature derived from Sun et al (SunlncSig) [24] using the same TCGA patient cohort. As shown in Figure 8, the AUC of overall survival for the GILncSig was 0.681, which was significantly higher than those of SunlncSig (AUC = 0.657) and LiulncSig (AUC = 0.656) (Figure 8).…”
Section: Performance Comparison In Terms Of Aucmentioning
confidence: 99%
“…Coincidentally, Zhang D, et al researched on LINC00460 as well. When identifying a three-lncRNA prognostic model [41], they speculated LINC00460's competing endogenous feature for its overexpression in ccRCC but did not mention its potential genomic instability. Controversially, the mutation frequency and expression did not exhibit to be consistently differential when quantitative analyses were performed (Figure 5), probably due to the uncertain carcinogenic mechanism in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, AC026356.2 and MELTF-AS1 were identi ed as immune-related lncRNA and showed a signi cant relationship with KIRC prognosis [22]. Zhang et al established a lncRNA prognostic model based on LINC00460, MIAT, and LINC00443 from a competitive endogenous RNA regulatory network constructed in KIRC [23]. The function of HOTAIRM1 in KIRC was reported by Hamilton et al [24].…”
Section: Discussionmentioning
confidence: 99%